Relationship of Peer-Friends Interaction with Interest in Student Learning - Fitri Fifolia Yunita; Riska Ahmad (Jurnal Neo Konseling, 2019)
Interest is one of the important factors in supporting students' understanding and success in learning. With the interest, students can more easily learn and understand the material conveyed by the teacher because students have an interest in teaching materials delivered by the teacher. However, the reality in the field is that there are students who have low interest in learning, there are still many students who do not pay attention to the teacher, are not interested in the lesson, do not like the lesson and lack of participation in learning. The interest in learning is the tendency of individuals to have pleasure without any coercion so that it can cause changes in knowledge, skills and behavior and it is thought that one of the factors that influence it is peer interaction. This research is a descriptive correlational research with quantitative methods. The total sample of 226 students was selected using the Simple Random Sampling technique. The research instruments used were peer interaction questionnaires and student learning interest questionnaires. The results of the study revealed that (1) peer interaction of students in Padang State Vocational High School 6 was in the good category. (2) students 'interest in learning at SMK Negeri 6 Padang is in a good category (3) there is a significant relationship between peer interaction with students' interest in learning at SMK Negeri 6 Padang. Based on research findings, it is recommended that school counselors / counselors be able to provide guidance and counseling services, namely information services and individual counseling services in order to help students who have problems with interest in learning